2016
DOI: 10.18203/2320-6012.ijrms20164528
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of post-vaccination anti-HBs titer and knowledge of hepatitis B infection amongst medical students in a metropolitan city

Abstract: INTRODUCTIONHepatitis B virus (HBV) infection is one of the major infectious diseases without seasonal distribution. 1 Medical students are at risk of acquiring HBV infection due to contact with patients' blood or other body fluids in healthcare or laboratory settings. 2 In the state of Maharashtra, 85% of medical students are admitted to the Bachelor of Medicine, Bachelor of Surgery (MBBS) course from various parts of Maharashtra while 15% are admitted through All-India quota. Hepatitis B vaccine is administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
2
6
4
Order By: Relevance
“…The Advisory Committee on Immunisation Practices (ACIP) has since 1997 recommended postvaccination serologic testing at least 1 – 2 months following last dose of vaccine to confirm immunity [ 15 ]. Previous studies among medical students have reported postvaccination serologic testing rates of 10 – 65% [ 18 , 21 , 22 ]. It is intriguing that none of our participants had measured antibody titres after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The Advisory Committee on Immunisation Practices (ACIP) has since 1997 recommended postvaccination serologic testing at least 1 – 2 months following last dose of vaccine to confirm immunity [ 15 ]. Previous studies among medical students have reported postvaccination serologic testing rates of 10 – 65% [ 18 , 21 , 22 ]. It is intriguing that none of our participants had measured antibody titres after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage of female protective responders was greater (85.5%) compared to male protective responders (75.9%), the association of anti-HBs status and gender was not statistically significant. Ashmaki et al, Chaudhari et al observed that anti-HBs titer due to gender factor was not statistically significant [22,23]. Also research studies have reported increased percentage of non-protective responders among males as compared to females [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…9 The percentage of completely vaccinated HCWs ranged from 40% to 49.6% across various Hospitals in India. [10][11][12] Two groups of HCWs were identified, first were those who were either partially vaccinated, non-vaccinated or had unknown status thus emphasizing an urgent need to implement a proactive Hepatitis B immunisation programme to improve protection against this infection and to achieve target of 90% vaccination coverage. 13 The second group included significant numbers of HCWs in booster dose vaccination category showing relatively good vaccination awareness and vaccination coverage in our hospital.…”
Section: Discussionmentioning
confidence: 99%